Gene expression profile in heat-shocked Holstein and Nelore oocytes and cumulus cells - Ticianelli, J. S. [UNESP] (2017)
The present study determined the transcriptome profile in Nelore and Holstein oocytes subjected to heat shock during IVM and the mRNA abundance of selected candidate genes in Nelore and Holstein heat-shocked oocytes and cumulus cells (CC). Holstein and Nelore cows were subjected to in vivo follicle aspiration. Cumulus-oocyte complexes were assigned to control (38.5°C, 22h) or heat shock (41°C for 12h, followed by 38.5°C for 10h) treatment during IVM. Denuded oocytes were subjected to bovine microarray analysis. Transcriptome analysis demonstrated 127, nine and six genes were differentially expressed between breed, temperature and the breed×temperature interaction respectively. Selected differentially expressed genes were evaluated by real-time polymerase chain reaction in oocytes and respective CC. The molecular motor kinesin family member 3A (KIF3A) was upregulated in Holstein oocytes, whereas the pro-apoptotic gene death-associated protein (DAP) and the membrane trafficking gene DENN/MADD domain containing 3 (DENND3) were downregulated in Holstein oocytes. Nelore CC showed increased transcript abundance for tight junction claudin 11 (CLDN11), whereas Holstein CC showed increased transcript abundance for antioxidant metallothionein 1E (MT1E) . Moreover, heat shock downregulated antioxidant MT1E mRNA expression in CC. In conclusion, oocyte transcriptome analysis indicated a strong difference between breeds involving organisation and cell death. In CC, both breed and temperature affected mRNA abundance, involving cellular organisation and oxidative stress.